G472 Use of Continuous Venovenous haemofiltration (CVVH) in patients with congenital metabolic disorders – A recent single-centre experience. (7th April 2014) - Nayak, P; Farley, M; Chakrapani, A; Hendricz, C
Abstract : Introduction: Congenital metabolic disorders are a rare but important cause of critical illness in children. Continuous venovenous haemofiltration (CVVH) is instituted as life-saving therapy for severe hyperammonaemia, metabolic acidosis and encephalopathy when conventional therapies fail. Practical challenges like obtaining vascular cathether access in low birth weight children are common. Some need liver transplantation and intra-operative CVVH to maintain acid-base balance. Significant comorbidities exist and determine the outcome in these patients. An understanding of their demographic and treatment profile is required for outcome prediction and service provision in these patients. Methods: Retrospective analysis of the Renal Replacement Therapy (RRT) database of a 31-bedded PICU over the past 3 years in a Children's Hospital in the UK. Results: 21 patients with congenital metabolic disorders had CVVH instituted. The median age was 7 years (2 days – 11 yrs) and weight 16 Kg (1.8 – 29.3). Propionic acidaemia and primary hyperoxaluria were two of the major diagnoses. Several indications for therapy were noted like severe metabolic and lactic acidosis, encephalopathy, acute liver / renal failures, rhabdomyolysis. 3 patients were significantly coagulopathic. All patients were invasively ventilated and 4 patients needed inotropic support. 4 patients underwent liver transplantation and needed intraoperative / postoperative CVVH. 2 patients also underwent Total Plasma Exchange on 4 occasions. Maximum serum ammonia was 1200. The median total duration of CVVH was 70 h (29 – 552). The median PICU length of stay was 4 days (1 – 29). 2 children died, both within the first 48 hrs of admission with multiorgan dysfunction. One of them had undergone liver transplant in the preceding 24 h. 4 patients who survived had an ongoing requirement for haemodialysis at time of PICU discharge. Conclusion: Patients with congenital metabolic disorders require CVVH when critically unwell, either at diagnosis or during subsequent admissions, often requiring prolonged therapy and PICU stay. Many patients have multiple admissions and some undergo organ transplant. This data would be helpful when identifying their levels of intensity of intensive care and service provision. There is a need for a national database of children undergoing RRT, of which those with congenital metabolic disorders form an integral part.